Lockdown Duration and Training Intensity Affect Sleep Behavior in an International Sample of 1,454 Elite Athletes - Romdhani, Mohamed; Fullagar, Hugh H. K.; Vitale, Jacopo A.; Nédélec, Mathieu; Rae, Dale E.; Ammar, Achraf; Chtourou, Hamdi; Al Horani, Ramzi A.; Ben Saad, Helmi; Bragazzi, Nicola Luigi; Dönmez, Gürhan; Dergaa, Ismail; et al. (Frontiers in Physiology, 2022)
Objective: To investigate the effect of (i) lockdown duration and (ii) training intensity on sleep quality and insomnia symptoms in elite athletes. Methods: 1454 elite athletes (24.1±6.7 years; 42% female; 41% individual sports) from 40 countries answered a retrospective, cross-sectional, web-based questionnaire relating to their behavioral habits pre- and during- COVID-19 lockdown, including: (i) Pittsburgh sleep quality index (PSQI); (ii) Insomnia severity index (ISI); bespoke questions about (iii) napping; and (iv) training behaviors. The association between dependent (PSQI and ISI) and independent variables (sleep, napping, and training behaviors) was determined with multiple regression and is reported as semi-partial correlation coefficient squared (in percentage). Results: 15% spent < one month, 27% spent 1-2 months and 58% spent > two months in lockdown. 29% self-reported maintaining the same training intensity during-lockdown whilst 71% reduced training intensity. PSQI (4.1±2.4 to 5.8±3.1; mean difference (MD): 1.7; 95% confidence interval of the difference (95% CI): 1.6 to 1.9) and ISI (5.1±4.7 to 7.7±6.4; MD: 2.6; 95% CI: 2.3 to 2.9) scores were higher during- compared to pre-lockdown, associated (all p<0.001) with longer sleep onset latency (PSQI: 28%; ISI: 23%), later bedtime (PSQI: 13%; ISI: 14%) and later preferred time of day to train (PSQI: 9%; ISI: 5%) during-lockdown. Those who reduced training intensity during-lockdown showed higher PSQI (p<0.001; MD: 1.25; 95% CI: 0.87 to 1.63) and ISI (p<0.001; MD: 2.5; 95% CI: 1.72 to 3.27) scores compared to those who maintained training intensity. Although the PSQI score was not affected by the lockdown duration, the ISI score was higher in athletes who spent > two months confined compared to those who spent < one month (p<0.001; MD: 1.28; 95% CI: 0.26 to 2.3). Conclusions: Reducing training intensity during the COVID-19-induced lockdown was associated with lower sleep quality and higher insomnia severity in elite athletes. Lockdown duration had further disrupting effects on elite athletes’ sleep behavior. These findings could be of relevance in future lockdown or lockdown-like situations (e.g., prolonged illness, injury, and quarantine after international travel).